Perancangan Strategi Pemasaran dan Peningkatan Kualitas Produk Pakan Burung pada IKM Sinar Mas Malang dengan Metode SWOT dan FMEA - Andrianus Herman Susanto; Purnomo (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2022)
This research focuses on designing marketing strategies and improving the quality of bird feed production at Sinar Mas, with the aim of maintaining marketing and increasing product sales. The study utilizes the SWOT and FMEA methods, with data collected from interviews and questionnaires over the past year. The current pandemic situation has brought challenges to Sinar Mas, making it necessary to propose alternative marketing strategies and quality improvement measures. The study proposes alternative marketing strategies based on the SWOT analysis and designs proper proposals for applying the FMEA method to improve the quality of Sinar Mas' products. The proposed measures include enhancing the marketing mix and designing a marketing strategy that is suitable for the current pandemic situation, including the use of digital marketing and optimizing social media platforms. Additionally, product quality improvements such as regular machine maintenance, improving packaging, and using high-quality ingredients are recommended. The study highlights the importance of continuously evaluating marketing strategies and product quality to maintain the competitiveness of IKMs in challenging situations. The findings of this study could be valuable for other small and medium industries facing similar challenges during the pandemic period.